Analisis Bauran Promosi Kopi Luwak di UD Cipta Lestari Desa Pujungan Kecamatan Pupuan Kabupaten Tabanan - DEWI, NI PUTU WINDA PURNAMI; YUSUF, RIA PUSPA; PARINING, NYOMAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.4, No.4, Oktober 2015, 2016)
Abstract Analysis of Promotion Mix Kopi Luwak at UD Cipta Lestari Pujungan Village Subdistrict Pupuan Tabanan Coffee is a kind of beverage derived from the coffee bean processing plants. Coffee classified into the genus Coffea Rubiaceae family. There are three known types of coffee plants in Indonesia including arabic coffee, robusta coffee and coffee Liberika. One of the products processed coffee produced and considered to have a huge business potential in Indonesia even in the world is the civet coffee. Kopi Luwak coffee is produced from the fermentation process through the stomach mongoose or weasel that eats ripe coffee cherries are then removed in the form of feces. This study aims to determine the promotional mix of civet coffee conducted by UD. Cipta Lestari which includes advertising, personal selling, sales promotion, public relations, and direct sales as well as to determine what the obstacles faced by the company in the application of the promotional mix. Methods of data collection in this study using observation , interviews , documentation and literature . The method used is descriptive qualitative analysis . The results showed that the company has already carried out promotions through all the variables of the promotional mix includes advertising, personal selling, sales promotion, public relations, and direct marketing as well as the obstacles faced by companies in the application of the promotional mix namely obstacles on promotional costs and shortages of raw materials. Keywords : promotion mix , civet coffee, direct marketing